Neuroprotective effects of omega-Aga-IVA against in vitro ischaemia in the rat hippocampal slice. - Small, D; Monette, R; Mealing, G; Buchan, A; Morley, P (1995)
Excessive accumulation of Ca2+ in neurones and glutamate release are involved in neuropathological processes, including ischaemia. We investigated the neuroprotective effects of the Ca2+ channel antagonist, omega-Aga-IVA, in CA1 pyramidal neurones in rat hippocampal slices following an in vitro hypoxic-hypoglycaemic insult. Following this insult, evoked post-synaptic response amplitudes decreased from 3.7 +/- 0.5 mV to 0.6 +/- 0.2 mV and the CA1 neurones appeared dead using a live/dead fluorescence assay with confocal microscopy. Slices treated with 200 nM omega-Aga-IVA had evoked response amplitudes not significantly different from control (3.3 +/- 0.5 mV) and the CA1 neurones appeared viable using the live/dead fluorescence assay. The neuroprotective efficacy of omega-Aga-IVA suggests that omega-Aga-IVA-sensitive Ca2+ channels participate in ischaemic neuronal death and constitute a potential target of therapeutic intervention.